Strobilanthes crispus leaves extracts (SCE) induced lipolysis and increased leptin level in diet-induced obese rats fed high-fat diet - Zawawi, Norhasnida; Abdul Hamid, Azizah; Ismail, Maznah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The aim of the present study was to assess the anti-obesity and lipolysis effects of Strobilanthes crispus leaves extract (SCE) in diet-induced obese (DIO) rats by administering 1% (w/w) of SCE in drinking water. Methods: Normal Sprague-Dawley rats were induced obese using a high-fat (HF) diet formulation for 14 weeks. DIO rats were subsequently treated with 1% (w/w) SCE while the HF diet was switched to normal rat chow diet. Food intake, water intake and bodyweight were measured weekly. Other parameters e.g. blood lipid profile were determined in normal and DIO rats before and after treatment with SCE. Histopathological changes in the liver were also observed after treatment. Results: Prior to treatment, DIO rats have significantly higher (p < 0.05) bodyweight, adipose tissue and liver weight, plasma leptin levels, lower adipose tissue lipolysis rate and severe fatty livers and the trend continues in non-treated DIO rats served as Control group. DIO rats treated with SCE significantly (p < 0.05) reduced their bodyweight gain, have lower adipose tissue and liver weight, lower leptin level and increased lipolysis rate although no significant effect was found in total bodyweights of treated group. Lower glucose level and improved state of fatty liver was also noted in SCE treated group. The observed anti-obesity effects are most likely the due to lipolysis. Conclusion: SCE may, at least in part, be attributed to the anti-obesity effects found on treated DIO rats.